Mesenchymal stem cell and microglia crosstalk in an inflammatory paradigm - Rahmat, Muhammad Zul'atfi (2013)
Stress or injury in the central nervous system (CNS) activates the resident immune cell, microglia. Chronic activation of microglia has been suggested to lead to progressive neuronal damages as the cells secrete excessive immune mediators. Managing the chronic responses of microglia may ameliorate inflammatory conditions of the CNS. As mesenchymal stem cells (MSC) have an immunomodulatory effect on a wide range of immune cells, this study aims to elucidate the immunomodulation of MSC on microglia during inflammation. For this, MSC isolated from mouse bone marrow were co-cultured with the immortalised microglia cell line (BV2) at 4 different seeding density ratios (1:0.2, 1:0.1, 1:0.02, 1:0.01; BV2:MSC), and stimulated with lipopolysaccharide (LPS). The reciprocal interactions of (i) MSC on microglia, (ii) microglia on MSC, and (iii) LPS on MSC were then examined. Crosstalk between these two cells was studied with an interest in understanding how MSC may respond to their cellular microenvironment. MSC increased nitric oxide (NO)expression at the 1:0.2 co-culture ratio (by 23.21 μM at 96 hrs, p<0.05, Tukey’s test), an effect where cell-cell contact was important. Crosstalk within this paradigm was exhibited by MSC producing their own NO (up to 75.51 ± 3.27 μM at 96 hrs, p<0.05, Tukey’s test) in response to signals conferred by soluble mediators of activated microglia. The effect of LPS on MSC was also demonstrated here, whereby MSC ‘primed’ with LPS were triggered to produce even larger amounts of NO (from 75.51 ± 3.27 μM to 103.41 ± 3.22 μM, p<0.05, Tukey’s test) subsequent to stimulation by BV2 mediators. MSC also inhibited proliferation of LPS-stimulated BV2 microglia (from 26468 ± 1714 cpm to 13080 ± 430.63 cpm, p<0.05, t-test) in a dose-dependent manner, as determined by tritiated thymidine incorporation. Soluble mediators from MSC were important for this anti-proliferative effect on BV2 microglia. Preliminary data also shows that priming MSC with LPS further drives their anti-proliferative effect on microglia (inhibiting proliferation to 27.41% compared to 38.03%). As determined by the BD Cytometric Bead Array, expression of IL-6 in cocultures increased to 1498.14 pg/ml compared to 288.79 pg/ml in microglia alone whilst TNF-α decreased from 3064.99 pg/ml to 1245.64 pg/ml. Expression of IFN-ƴ, IL-10 and IL-12p70 were unremarkable in any of the treatments. It is interesting to note that the immunoregulation of MSC on BV2 microglia is not conferred by the anti-inflammatory cytokine IL-10. Although expression of the chemokine MCP-1 was high in activated BV2 microglia and primed MSC, there were no significant changes in co-cultures. By examining the reciprocal interactions of MSC and microglia, this study exhibits the cellular responses of both cell types which may lead to the discovery of regulatory mechanisms conferred by MSC.